Phase II trial of Pemetrexed plus Gemcitabine in patients with advanced non-clear cell renal cell carcinoma - Richey, Stephen L (2013)
OBJECTIVE: To determine the clinical activity and toxicity of combination pemetrexed and gemcitabine for locally advance and metastatic non-clear cell renal cell carcinoma. METHODS: In this phase II study patients were treated with pemetrexed 500 mg/m(2) IV infusion over 10 minutes(min) on day one followed immediately by gemcitabine 1500 mg/m(2) IV over 30 min on day one, repeated every fourteen days. Planned enrollment was 40 patients. The primary endpoints were response rate and progression free survival (PFS). The secondary endpoints were toxicity and overall survival (OS) in months (mo). RESULTS: Between December 2005 and December 2008, 16 patients with locally advanced or metastatic non clear cell renal cell carcinoma were enrolled. The trial was stopped due to lack of response and excessive toxicity. The overall response rate was 6.7% (95% exact CI: 0.2%–31.9%), no patients with renal cell carcinoma responded to therapy. The median number of cycles administered was 4 (range: 1–12 cycles), median PFS was 3.2 mo (95% CI: 1.875–>6 mo), and the 16-week PFS rate was 46.7% (95% CI: 19.8%–100%). The median OS was 23.2 mo (95% CI: 12.9–38.1 mo). The most common grade 3 or 4 toxicities were neutropenia (53%), leukopenia (53%), anemia (13%), fatigue (40%), and renal failure (13%). CONCLUSIONS: Patients with non clear cell carcinoma metastatic renal cell carcinoma. The combination of pemetrexed and gemcitabine did not show clinical activity in this cohort of patients with non clear cell renal cell carcinoma.